2019
DOI: 10.22435/mpk.v29i2.875
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Ramuan Ekstrak Biji Klabet dan Daun Kelor sebagai Laktagogum dengan Nilai Gizi Tinggi

Abstract: Abstract The proportion of stunting in children under 5 years old in Indonesia was approximately 30,8% in 2018. One of the things that is presumably related to the occurrence of stunting is lack of nutrition that can be attributed to exclusive breastfeeding. Fenugreek seeds have properties as laktogoga and moringa leaves in addition to having efficacy as lactagoga, also have advantage in nutritional content, particularly high protein content, groups of minerals and vitamins. The aim of the study was to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
0
2
0
6
Order By: Relevance
“…The fat content obtained does not meet the quality requirements for the fat content of ice cream and the fat intake requirements for each individual in a day according to the POM (Food and Drug Monitoring) so it is necessary to consume other food ingredients that contain fat sources. Furthermore, fat has a role as the largest source of energy for the body (Widowati et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The fat content obtained does not meet the quality requirements for the fat content of ice cream and the fat intake requirements for each individual in a day according to the POM (Food and Drug Monitoring) so it is necessary to consume other food ingredients that contain fat sources. Furthermore, fat has a role as the largest source of energy for the body (Widowati et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effect is a function of dose and time, such charts illustrate the dose-response relationship that is not time-dependent. In this situation the maximum effect intensity (ceiling effect) can be caused 22 . In this condition, it can also be concluded that the dose of moringa leaf nanoparticles which can cause an effect that is an increase in zygote cleavage is at a dose of> 2.0 μM while the doses of 0.5 μM and 1.0 μM do not have pharmacological effects in this case do not support embryonic cell cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Kedua bahan yang digunakan dalam penelitian ini merupakan galactagogue herbal yang dapat meningkatkan kualitas dan kuantitas ASI. Mekanisme daya galactagogue suatu senyawa dapat terjadi antara lain melalui rangsangan secara langsung pada aktivitas protoplasma sel˗sel sekretoris kelenjar susu, rangsangan ujung saraf sensoris di dalam kelenjar susu sehingga sekresi air susu meningkat, atau rangsangan hormon prolaktin yang bekerja pada sel˗sel epitelium alveolar (26).…”
Section: Pembahasanunclassified